The Lille apathy rating scale (LARS), a new instrument for detecting and quantifying apathy: validation in Parkinson's disease. Issue 5 (13th April 2006) - Sockeel, P; Dujardin, K; Devos, D; Denève, C; Destée, A; Defebvre, L
Abstract : Background: Apathy is usually defined as reduced interest and participation in various activities. It is a frequent consequence of neurological and psychiatric disorders. Although various scoring methods have been proposed, there is a lack of validated, standardised instruments for detecting apathy and assessing its severity. Objective: To develop an apathy rating scale using a structured standardised interview capable of distinguishing between the condition's various features. Methods: The Lille Apathy Rating Scale (LARS) is based on a structured interview. It includes 33 items, divided into nine domains. Responses are scored on a dichotomous scale. The participants used to validate the scale consisted of 159 patients with probable Parkinson's disease and 58 healthy control subjects. The Marin Apathy Scale, the Montgomery and Asberg Depression Rating Scale, and the Mattis Dementia Rating Scale were also administered. Results: Principal component analysis showed that the LARS probed a single construct which forms the root of an oblique factor structure reflecting four dimensions: intellectual curiosity, self awareness, emotion, and action initiation. The main psychometric properties of the LARS (internal consistency, inter-rater and test-retest reliability) were satisfactory. Concurrent validity was evaluated by reference to the Marin scale and to judgements provided by expert clinicians. Conclusions: Standard validity indices showed that the LARS is sensitive and capable of distinguishing between apathy and depression. As a screening tool, the scale is able to support dichotomous judgements accurately and, when greater measurement sensitivity is required, also determine the severity of apathy within a four category classification.